O mapa social : o germinar e o florescer de uma metodologia participativa e decolonial - Amorim, Aleth da Graça Amorim (2020)
This research focused on the study of the ten years (2008-2018) of the project and the research methodology "Social Map", it sought to know its methodological aspects, the principles, academic and popular productions and the possibilities that this methodology offers as a participatory and decolonial proposal. The ten-year period was adopted, which encompasses the emergence of the methodology in 2008 until the researcher's entry into the master's degree in 2018. A qualitative research of a participant nature was carried out with a focus on the self-narratives of the people involved in the processes of the Social Map , evidencing their experiences, their perceptions and understandings about the dazzle of the Social Map in their communities, in their life and in their research. For this, participant observations and eleven semi-structured interviews were carried out, in addition to a bibliographic survey of the productions related to the Social Map, in the ten years that comprise the study, registering two doctoral theses, four master's dissertations, 03 pedagogical notebooks, 01 book and other publications. The Social Map, since its birth, together with the Research Group on Environmental Education, Communication and Art (GPEA) of the Federal University of Mato Grosso (UFMT) and its various partners, as a research project until its consolidation as a research methodology, reflects a collaborative process. Far from being ready and finished, but as a methodological light of participatory and decolonial work. It brings with it the roots with the principles of Critical Environmental and Community Based Education and Decoloniality, since it is an important instrument of denunciation and announcement of the flames of resistance and the reexistence of the peoples and communities of Mato Grosso. This methodology allows to denounce the violations of human rights, the socio environmental impacts, the conflicts, the vulnerabilities in which the communities are found, in addition to allowing the reflection of themes of the communities' daily life, encouraging a thinking and doing that reflect the territorial plots, the common meanings and the challenges of socio-environmental sustainability of the territory. The Social Map unfolds in resistance tactics, subsidies to the elaboration of public policies and human rights reports, showing an active and committed Environmental Education in the construction of a fairer world, announcing the diversity of peoples, their visibility and their struggles.